The impact of digitalization in the business model innovation - Matheus de Almeida Martins (2021)
Digitalization is present in our daily lives more than we may realize, although conventionally we know that much of what we do today is intrinsically connected to digital tools. The same happens for companies that, with each passing day, need to be innovating and applying technology to their products and processes. Despite the convention that technology is increasingly present in companies, there is little evidence of the impacts caused by digitalization on business models. The objective of this study is to understand and analyze what are, currently, the main impacts that digitalization can bring to business model innovation. Thus, it will be possible to identify the business opportunities present in companies in order to change their operation in a positive way. For the execution of this research, we developed a framework containing the impacts and opportunities that digitalization can bring to a business and how it is possible to apply these opportunities to a business through a tool called Digitalization Opportunity Deck of Cards. To validate the proposed framework and the tool created, we analyzed a startup from Porto, Portugal, focused on the production of healthy meals sold over the internet. The analysis and discussion with the entrepreneurs allowed us to identify changes in each of the components of the business model that will be impacted by digitalization, so that the current business model will suffer some changes to adapt to the digital world.